Humanism in medicine - Kaleka, Kultaj (The International Journal of Whole Person Care, 2021)
The piece is an essay or reflection on the importance of humanism in medicine. The author encourages clinicians, first and foremost, to consider their relationship with patients from the vantage point of a shared humanity. This view allows for a better understanding of patients' needs and ensures patient-centered care.